Islamic Boarding School Journalism As a Way of Strengthening Literacy Culture - Rio Kurniawan; Lian Agustina Setiyaningsih; Imam Sofyan (MediaTor (Jurnal Komunikasi), 2022)
Islamic boarding schools (pesantren) can be a locus of change concerning technology and journalism. Values and traditions in pesantren are a challenge in the practice of internalising a new culture. This study aims to formulate a pattern of internalisation in journalistic literacy culture based on local wisdom. The research method used is descriptive qualitative with a constructivism paradigm. Data collection techniques used in-depth interviews, observations, and literature reviews. The purposive sampling technique resulted in three informants related to journalistic activities at Darul Ulum Islamic Boarding School Banyuanyar Pamekasan. The methods of data analysis used are based on Miles and Huberman. The study results showed that the internalisation of literacy culture used traditional methods by extracting the value of journalistic literacy and applying it to make Islamic religious students (santri) cadres maintain journalistic values. There is also a categorisation of journalistic literacy skills. The internalisation of journalistic literacy culture started from developing wall magazines, Ikhwan magazines, online journalism forums, namely Forum Lingkar Pena (FLP), journalistic training, and alumni networks. Meanwhile, the study's recommendation is to develop a pattern of internalisation for journalistic literacy culture based on local values (local wisdom).